The Effect of Gasoline Price on Economic Sectors in Nigeria - Nwosa, Philip Ifeakachukwu; Ajibola, Akinyemi Alao (International Journal of Energy Economics and Policy, 2012)
This paper examined the long-run and short-run relationship between gasoline price and sectoral output in Nigeria for the period from 1980 to 2010. Six sectors (agriculture; manufacturing; building and construction; wholesale and retail; transportation and communication) of the economy were examined. The long run regression estimate showed that gasoline price is a significant determinant output in all sectors examined with exception to the building and construction sector while the short run error correction estimate revealed that only output of the agriculture and the manufacturing sectors of the Nigerian economy is affect by gasoline price increase in the short run. The study recommended among others the need for the government to ensure adequate power supply in order to reduce the over reliance of economics sectors on gasoline as a prime source of power. Keywords: Gasoline Price; Sectoral Output; Error-Correction Method; Nigeria. JEL Classifications: Q43